Development and evaluation of a low cost power operated paddy thresher - um- winnower - SURESHKUMAR P. K; Er. Sankaranarayanan M. R (Guide) (Tavanur 1996 Kelappaji College of Agricultural Engineering and Technology)
Development and evaluation of a low cost power operated paddy thresher - um- winnower
Development and evaluation of a low cost power operated paddy thresher - um- winnower